Characterisation of Trypanosomal Type III and Type IV Hsp40 proteins - Louw, Cassandra Alexandrovna (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2009)
The heat shock protein-70 (Hsp70) family of molecular chaperones are ubiquitous highly conserved proteins that are critical for the viability of cellular homeostasis. The ATPase activity of Hsp70 proteins is critical to their function as the affinity of a given Hsp70 for non-native substrate is modulated by ATP binding and hydrolysis. When bound to ATP, Hsp70s possess a low affinity for a given substrate protein, while the hydrolysis of ATP to ADP causes a conformational change that results in a high affinity for substrate proteins. The basal ATPase activity of Hsp70s is too low to facilitate their function in vivo, and co-chaperones are essential to modulate the efficient protein folding by Hsp70. Heat shock protein-40 (Hsp40) heat shock proteins are essential for the in vivo function of Hsp70s by stimulating the ATPase activity of these proteins and facilitating transfer of substrates. The Type III class of Hsp40 proteins have not been well characterised due to their poor levels of conservation at the primary sequence level. This is due to the fact that Type III Hsp40s only contain a J-domain and a poorly conserved C-terminal region. The newly identified Type IV class of Hsp40s, contain an abrogated HPD tripeptide motif in the J-domain and have also not been extensively studied. Trypanosoma brucei (T. brucei) is a unicellular flagellated protozoan parasite. It is the causative agent of Human African Trypansomiasis (HAT) which results in thousands of deaths and devastating agricultural losses in many parts of Africa. T. brucei undergoes a complex lifecycle that is characterised by the transition from an insect vector to a mammalian host in markedly different conditions of temperature, pH, nutrient availability and respiratory requirements. It has been proposed that molecular chaperones may enhance the survival of these parasites due to their cytoprotective effect in combating cellular stress. Due to the fact that T. brucei infection is invariably fatal if left untreated, and that no novel treatment regimens have been developed recently, the identification of potential novel drug targets among proteins essential to the parasite's survival in the host organism is an attractive aspect of T. brucei research. Because Type III Hsp40s are poorly conserved with respect to Hsp40s found in the human host, the identification of any of these proteins found to be essential to T. brucei survival in humans could potentially make attractive novel drug targets. An in depth in silico investigation into the Type III Hsp40 complement as well as partner Hsp70 proteins in T.brucei was performed. T. brucei possesses 65 Hsp40 proteins, of which 47 were classed as Type III and 6 of which were identified as being putative Type IV Hsp40s. A small but significant number (5) of Type III TbHsp40s contained tetratricopeptide (TPR) domains in addition to the J-domain. The J-domains of the Type III TbHsp40 complement were found to be conserved with respect to those of canonical Hsp40 proteins, although the mutation of certain residues that play a key role in Hsp40-Hsp70 interaction was noted. Potential partnerships of these proteins in the parasite was also investigated. The coding regions of three previously uncharacterised TbHsp40s were successfully amplified from T. brucei TREU927 genomic DNA and cloned into an expression vector. Tbj1, a Tcj1 ortholog, was selected for further study and successfully expressed and biochemically characterised. Tbj1 expressed in E. coli was found to be insoluble, but large amounts were recovered with the aid of a denaturing purification followed by refolding elution strategies, and the bulk of the protein recovered was in compact monomeric form as determined by size-exclusion chromatography fast protein liquid chromatography (SEC-FPLC). The addition of Tbj1 to a thermally aggregated substrate resulted in increased levels of aggregation, although Tbj1 was able to assist two Hsp70 proteins in the suppression of aggregation. Tbj1 proved unable to stimulate the ATPase activity of these same Hsp70s, and could not rescue temperature sensitive cells when replacing E.coli DnaJ and CbpA. It was concluded that Tbj1 does not possess independent chaperone activity, but could display Hsp40 co-chaperone properties under certain circumstances. This could allude to a specialised function in the T. brucei parasite. The lack of human orthologues to Tbj1 could result in the attractiveness of this protein as a novel drug target.
Keywords: Trypanosoma; Heat shock proteins; African trypanosomiasis; Epidemic encephalitis